2016
DOI: 10.1007/s00268-016-3466-5
|View full text |Cite
|
Sign up to set email alerts
|

The Damage Pattern to the Gastrointestinal Tract Depends on the Nature of the Ingested Caustic Agent

Abstract: Bleach causes mild gastrointestinal injuries, while the ingestion of strong acids and alkalis may result in severe complications and death. Acids cause more severe damage to the stomach but similar damage to the esophagus when compared to alkalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
0
7
0
6
Order By: Relevance
“…However, later endoscopic study contradicted this notion by showing that among acid ingestion patients, esophageal injury was seen in 87.8% and gastric injury in 85.4% of the patients[ 6 ]. Recent evidence indicated that acid ingestion caused more injury to the stomach (31% vs 13%) while the incidence of esophageal injury was similar between acid and alkali ingestion[ 7 ]. Gastroesophageal reflux from impaired lower esophageal sphincter function[ 8 ] and loss of esophageal motility[ 9 ] are also results of a caustic damage to the esophagus.…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, later endoscopic study contradicted this notion by showing that among acid ingestion patients, esophageal injury was seen in 87.8% and gastric injury in 85.4% of the patients[ 6 ]. Recent evidence indicated that acid ingestion caused more injury to the stomach (31% vs 13%) while the incidence of esophageal injury was similar between acid and alkali ingestion[ 7 ]. Gastroesophageal reflux from impaired lower esophageal sphincter function[ 8 ] and loss of esophageal motility[ 9 ] are also results of a caustic damage to the esophagus.…”
Section: Pathophysiologymentioning
confidence: 99%
“…1,3 O tipo de produto envolvido varia de acordo com a região geográfica, mas os mais frequentes são hipoclorito de sódio, presente em alvejantes e desinfetantes (água sanitária), e hidróxido de sódio (soda cáustica), presente em detergentes, limpa-fornos, sabões artesanais, baterias e cosméticos. 1,2 Em nosso meio, levantamento epidemiológico realizado na Unidade de Toxicologia do Hospital João XXIII da Fundação Hospitalar de Minas Gerais descreve atendimento de cerca de 13.293 pacientes no ano de 2015, sendo 5.656 destes crianças e adolescentes.…”
Section: Desenvolvimento Livre Epidemiologiaunclassified
“…Um produto ingerido pode conter múltiplos agentes potencialmente cáusticos e, por isso, é importante consultar um centro de toxicologia para planejamento do tratamento. 1,2,7 O exame físico permite a detecção de lesões orais, além de sinais sugestivos de complicações, como instabilidade hemodinâmica, dispneia e enfisema subcutâneo. 1,2…”
Section: Desenvolvimento Livre Epidemiologiaunclassified
See 2 more Smart Citations